Detection of explosives - Dovbnya, A.N.; Yegorov, A.M.; Zhuk, V.V.; Pugachev, G.D.; Shapoval, I.I.; Shepelev, A.G. (Вопросы атомной науки и техники, 2006)
The extensive literature on the methods of detection of explosives under the stationary and field conditions is reviewed.
Today, there are hundreds of publications on detectability of explosives by different methods, but none of
the methods gives a 100% guarantee of explosives detection. Consideration has been given to advanced high-technology
methods of explosives detection: nuclear quadrupole resonance method, nuclear physics methods (slow and
fast neutrons, gamma-quanta), biological methods. Notice that the danger of newly created explosives, including
land mines, increases. The actuation systems are also constantly improved. Most difficulties with detection, extraction
and deactivation of explosive devices can be overcome with the help of updated methods and techniques. The
present review calls attention primarily to the possibility of solving the pressing and complicated problems using
charged particle accelerators. Проведен обзор литературы по методам детектирования взрывчатых веществ (ВВ) в стационарных и полевых условиях. В настоящее время имеются сотни публикаций по возможности детектирования ВВ различными методами, но 100% гарантии их обнаружения нет. Внимание уделено современным высокотехнологическим методам обнаружения ВВ: ядерному квадрупольному резонансу, ядерно-физическим (медленные и быстрые нейтроны, гамма-кванты) и биологическим. Следует отметить, что опасность вновь создаваемых ВВ, в том числе и полевых мин, увеличивается. Совершенствуются и системы их срабатывания. Большинство трудностей по детектированию, извлечению и деактивации взрывных устройств может быть преодолено с помощью современных методов и технологий. Данный обзор, прежде всего, обращает внимание на возможность решения этой острой и сложной проблемы с помощью ускорителей заряженных частиц. Проведено огляд літератури по методах детектування вибухових речовин (ВР) у стаціонарних і польових
умовах. На даний час є сотні публікацій по можливості детектування ВР різними методами, але 100%
гарантії їх виявлення немає. Увага приділена сучасним високотехнологічним методам виявлення ВР:
ядерному квадрупольному резонансу, ядерно-фізичним (повільні й швидкі нейтрони, гамма-кванти) і
біологічним. Слід зазначити, що небезпека створюваних ВР, у тому числі польових мін, збільшується.
Удосконалюються й системи їхнього спрацьовування. Більшість труднощів по детектуванню, добуванню і
деактивації вибухових пристроїв може бути подолане за допомогою сучасних методів і технологій. Даний
огляд, насамперед, звертає увагу на можливість рішення цієї гострої і складної проблеми за допомогою
прискорювачів заряджених частинок.